2020
DOI: 10.26630/jk.v11i1.1465
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Faktor Risiko Dermatitis Kontak pada Petani

Abstract: Farmers are generally always exposed to chemicals in the form of pesticides and fertilizers which can be irritants and allergens. This research was an observational descriptive using a cross-sectional method with 379 respondents. The research data were taken from interviews, questionnaires, and physical examinations by dermatologists and genitals. Data were analyzed using the chi-square test. Results: 13,5% of farmers experienced contact dermatitis. The analysis results of this study indicate that there is a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 3 publications
(3 reference statements)
0
5
0
3
Order By: Relevance
“…This research is in accordance with research that has been conducted by farmers with Dermatitis who have poor personal hygiene as many as 20 people (32.5%), who have good personal hygiene as many as 17 people (24.6%) and who have very good personal hygiene as many as 14 people (5%). Based on these data it can be concluded that farmers who experience dermatitis are more in the group of farmers who have poor personal hygiene (Rahmatika et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This research is in accordance with research that has been conducted by farmers with Dermatitis who have poor personal hygiene as many as 20 people (32.5%), who have good personal hygiene as many as 17 people (24.6%) and who have very good personal hygiene as many as 14 people (5%). Based on these data it can be concluded that farmers who experience dermatitis are more in the group of farmers who have poor personal hygiene (Rahmatika et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Personal hygiene is very important for farmers because it prevents germs from sticking to clothes and bodies of farmers who are exposed to sweat or even other chemicals such as pesticides, fertilizers, etc. Personal hygiene experienced by farmers has decreased due to wrong bathing habits, washing clothes, clothes used, inappropriate rules for washing hands and feet or not even using soap and using running water (Rahmatika et al, 2020). Wrongly caused by several factors experienced by farmers.…”
Section: Discussionmentioning
confidence: 99%
“…Di sisi lain, penelitian dari Munawar (2020) menunjukkan bahwa sebesar 53,6% proporsi dermatitis kontak terjadi pada petani [7]. Demikian juga hasil penelitian dari Rahmatika et al (2020) menemukan bahwa proporsi dermatitis kontak pada petani sebesar 13,5% [8].…”
Section: Pendahuluanunclassified
“…Dari hasil penelitian yang mempunyai riwayat atopi maupun tidak memiliki kesempatan yang sama untuk terjadinya dermatitis kontak, hasil ini tidak sesuai dengan penelitian sebelumnya bahwa tidak ada hubungan antara riwayat atopi dengan kejadian dermatitis kontak, sehingga semua petugas memiliki risiko yang sama untuk mengalami dermatitis kontak. 20,21 Hasil analisis multivariate secara keseluruhan besarnya kontribusi variable penggunaan APD, riwayat atopi dan jenis pekerjaan dalam memprediksi kejadian dermatitis kontak iritan sebesar 64,2% untuk pengaruh variable lain di luar penelitian sebesar 35,8%.…”
Section: Tingkatunclassified